Path Analysis of Factors Affecting the Quality of Life of Hypertensive Patients At the Mandai Health Center - mansur sididi; andi mappanganro; andi batari salsabila; nur hikmah (Preventif : Jurnal Kesehatan Masyarakat, 2026)
Hypertension is one of the diseases that is considered the main cause of death and disability. The incidence rate of hypertension increases rapidly every year. This study aims to determine the influence of long-term suffering from hypertension, family support and medication adherence to the quality of life of patients through smoking behavior at the Mandai Health Center, Maros Regency. The type of research used is quantitative research with a cross sectional study design, which is a research design that studies the relationship between independent and dependent variables. The population in this study is all hypertension patients in the working area of the Mandai Health Center as many as 100 people. The sample in this study was 100 people using the sampling technique, namely total sampling. Statistical analysis used univariate and bivariate, with the chi square test followed by the path analyst.  The results of the study using pathway analysis showed that family support (p=0.004, β=0.279), medication adherence (p=0.011, β=-0.0274) had a significant effect on the quality of life of hypertensive patients while suffering for a long time (p=0.0.357, β=0.098), and smoking behavior (p=0.960, β=-0.005) did not have a significant effect on the quality of life of hypertensive patients at the Mandai Health Center, Maros Regency.  The suggestion in this study is that it is expected that the patient's family will always support the treatment of hypertension patients so that the level of adherence to taking medication is better.